APPLICATION OF ESSENTIAL OILS FROM TWO SPECIES OF THE RUTACEAE FAMILY AS CELLULAR OXIDATION CONTROLLER AGENT AND TRYPANOCIDAL CAPACITY - JL, CORREA CALEÑO; Ospina Cc, Cerquera; W, MURILLO ARANGO; JJ, MÉNDEZ ARTEAGA; Perea e, Murillo (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Abstract The essential oil isolated by hydrodistillation from peel of Citrus aurantium and Swinglea glutinosa, collected from IbaguÃ©-Province of Tolima-Colombia (South America), was analyzed by GC/MS. The major compounds identified in essential oil of S. glutinosa were germacrene-D (30.8%), Î²-pinene (22.6%) and sabinene (11.6%), while limonene (94.4%)was identified as the most abundant component in C. aurantium.The ability of these products and mixturesto control cellular oxidation and measure theiranti-epimastigotes of Trypanosoma cruzi activity, the protozoan Chagas transmitter,were investigated.Besides, the type ofdrug interactionbetweenessential oil mixtureswas determinedby the values ofcombination index, which indicated for all cases the existence of a strong antagonism between the mixtures prepared.According to ABTS assay, Î²-carotene bleaching test andprotective activityagainst erythrocytes degradationshowed that volatiles compounds have a wide spectrum as cellular oxidation controller.This is the first time, that oils of S. glutinosa andÂ C. aurantium, have high activity againstÂ T. cruzi, in vitro; capacity that could be directly associated to the chemotype of they, one of which (Swinglea glutinosa) appears not to be found in other research. Â Keywords Essential oil composition, Citrusaurantium, Swingleaglutinosa, ABTS, Rutaceae. Â